2020
DOI: 10.1111/zph.12743
|View full text |Cite
|
Sign up to set email alerts
|

First glimpse into the origin and spread of the Asian longhorned tick, Haemaphysalis longicornis, in the United States

Abstract: Established populations of Asian longhorned ticks (ALT), Haemaphysalis longicornis, were first identified in the United States (US) in 2017 by sequencing the mitochondrial cytochrome c oxidase subunit I (cox1) ‘barcoding’ locus followed by morphological confirmation. Subsequent investigations detected ALT infestations in 12, mostly eastern, US states. To gain information on the origin and spread of US ALT, we (1) sequenced cox1 from ALT populations across 9 US states and (2) obtained cox1 sequences from potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 57 publications
0
53
0
Order By: Relevance
“…In New Jersey, among more than the 1100 ticks collected from the index site, only one male specimen was found, indicating that the invasive population was parthenogenetic [16]. This was supported by a genetic analysis, which indicated H. longicornis ticks in the United States are more similar to those of parthenogenetic populations than those of bisexual populations [24]. The parthenogenetic populations are distributed in Australia, New Zealand, New Caledonia, Fiji, New Hebrides, Tonga, northeastern Russia, northern Japan, Kyushu and Yakushima in southern Japan, and Sichuan and Shanghai in China [1,25,26].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In New Jersey, among more than the 1100 ticks collected from the index site, only one male specimen was found, indicating that the invasive population was parthenogenetic [16]. This was supported by a genetic analysis, which indicated H. longicornis ticks in the United States are more similar to those of parthenogenetic populations than those of bisexual populations [24]. The parthenogenetic populations are distributed in Australia, New Zealand, New Caledonia, Fiji, New Hebrides, Tonga, northeastern Russia, northern Japan, Kyushu and Yakushima in southern Japan, and Sichuan and Shanghai in China [1,25,26].…”
Section: Introductionmentioning
confidence: 76%
“…Haemaphysalis longicornis has most likely come to North America from East Asia [24]. Companion animals (particularly dogs) entering the United States are thought to be the source [24]. Based on our habitat suitability models, the geographic distribution of the H. longicornis will likely continue to expand in North America.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The previous detection of T. orientalis Ikeda in H. longicornis, but not native ticks, from the same area in VA provides further support for this hypothesis [33]. H. longicornis has already spread to at least fourteen U.S. states [27,28,35], survives well in varied environmental conditions [24,27,28,35], and exhibits a wide array of host feeding preference [24], including deer and avian species [25,27,28,35]. Given the cosmopolitan nature of the tick vector, there is signi cant potential for extensive, rapid spread of T. orientalis Ikeda throughout the U.S. due to movement of infected, asymptomatic cattle.…”
Section: Discussionmentioning
confidence: 68%
“…In conclusion, we have demonstrated that a U.S. population of the invasive Asian longhorned tick, H. longicornis, is a competent vector of the T. orientalis Ikeda genotype isolated from a beef herd outbreak in VA, U.S. in 2017 [23]. Since the Asian longhorned tick has become established in fourteen U.S. states [25,28,35], and many T. orientalis-infected cattle exhibit only mild, intermittent clinical signs, there is signi cant potential for T. orientalis Ikeda to spread widely within the expanding North American range of H. longicornis in the absence of surveillance and livestock tick control measures throughout this and neighboring regions. Furthermore, the development and implementation of improved diagnostic assays for T. orientalis surveillance may be needed to reduce losses incurred by the U.S. cattle industry.…”
Section: Discussionmentioning
confidence: 76%